Bicortical Versus Unicortical Pedicle Screws in Direct Vertebral Rotation An In Vitro Experimental Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Study Design: In vitro experimental study. Objective: This study aimed to evaluate the biomechanical properties of bicortically placed and laterally oriented screws, which may represent an alternative approach for challenging sites during direct vertebral rotation (DVR). Summary of Background Data: DVR corrects the transverse plane deformity and the thoracic hump in idiopathic scoliosis. However, instrumentation of the convex side of the scoliosis apex may pose a challenge, not allowing the placement of suitable sized screws in adequate direction. Methods: Forty-eight calf vertebrae were used and each vertebral body was instrumented with 1 pedicle screw as follows: unicortical group (n = 16), a short screw was unicortically placed and directed laterally; bicortical group (n = 16), a short screw was bicortically placed again in lateral direction; control group (n = 16), a screw with ideal length and direction was placed. Vertebral bodies were rigidly anchored in a custom device. Each screw was rotated using a constant length lever arm while collecting force to failure data. Results: Significantly better results were obtained with bicortical screwing when compared with unicortical screwing (335.4 +/- 45.6 vs. 239.5 +/- 58.50 N, P < 0.001). However, mean force to failure was significantly higher in the controls than in the bicortical group (415.8 +/- 49.2 vs. 335.4 +/- 45.6 N, P < 0.001). Conclusions: Bicortical screw placement may provide a biomechanically superior construct than unicortical screw placement for resisting DVR maneuver during scoliosis correction. This technique may represent an effective and safe approach, particularly for the convex side of the scoliosis apex, with increased resistance to derotational forces and decreased risk of bone failure. Further clinical studies are warranted for firmer conclusions.
Keywords: direct vertebral rotation; bicortical pedicle screw; unicortical pedicle screw; scoliosis; force to failure; ADOLESCENT IDIOPATHIC SCOLIOSIS; THORACIC SPINE; RETROSPECTIVE ANALYSIS; COMPUTED-TOMOGRAPHY; FIXATION; INSTRUMENTATION; SURGERY; COMPLICATIONS; DEROTATION; FUSION